Predicting Exit, Voice, Loyalty, and Neglect - Withey, Michael J.; Cooper, William H. (Administrative Science Quarterly, 1989)
This paper is based on a dissertation completed by the first author under the supervision of the second. We thank Hugh Arnold, Julian Barling, Carol Beatty, John Dowling, Vic MacDonald, and Don Nightingale for their help at the thesis stage, two very thoughtful ASO reviewers, Dan Farrell and Janet Near for their comments on an earlier version of the paper, Tom Mahaffey for a timely question, and Ted Neave for getting things started. Financial support to the second author was provided by the Social Sciences and Humanities Research Council of Canada (SSHRCC 494-88-1015). This paper reports the results of two longitudinal studies we conducted to find out when dissatisfied employees will respond to their dissatisfaction with exit, voice, loyalty, or neglect. We found consistent evidence that exiters were affected by the costs and the efficacy of their responses as well as the attractiveness of their employing organization. Loyalists were primarily affected by the efficacy of their responses, although, unexpectedly, loyalty resembled entrapment in the organization more than it did supportive allegiance to the organization. Neglecters were primarily affected by the costs and the efficacy of their responses, and voicers were very difficult to predict. We conclude by arguing that we need a much better understanding of voice and loyalty in order to predict better how employees will respond to dissatisfaction.'